Development of a Game-Assisted Flipbook to Enhance Fifth-Grade Students’ Conceptual Understanding of Cultural Diversity - Ni Ketut Somantari; I Made Citra Wibawa; Ketut Suma (Universitas Pendidikan Mandalika, 2026)
This study aims to develop and evaluate the feasibility, practicality, and effectiveness of a game-assisted flipbook on cultural diversity for fifth-grade elementary school students. The study was conducted in Cluster V Tuanku Imam Bonjol, Denpasar, Bali, using the ADDIE development model. The participants included two content experts, two media experts, 12 teachers, and 65 fifth-grade students, comprising 33 students in the experimental group and 32 in the control group. Data were collected using expert validation sheets, teacher and student practicality questionnaires, and pretest–posttest assessments of concept mastery. The data were analyzed using descriptive statistics, percentage conversion, analysis of covariance (ANCOVA), and normalized gain (N-gain). The flipbook was developed using Microsoft Word, Canva, and Heyzine, and featured contextual narratives, cultural illustrations, reflective activities, QR codes, and educational games. The validation results indicated that the product was highly feasible, with a mean score of 3.87 (96.75%) from both content and media experts. Practicality was also rated very highly, with scores of 3.84 (95.88%) from teachers and 3.91 (97.83%) from students. ANCOVA results revealed a statistically significant difference between the experimental and control groups after controlling for pretest scores (F = 84.980, p < 0.001), with a large effect size (partial eta squared = 0.578). Furthermore, the N-gain analysis showed greater improvement in the experimental group (0.81, high category) compared to the control group (0.51, moderate category). In conclusion, the game-assisted flipbook is highly feasible, practical, and effective in improving students’ concept mastery in elementary education.